2013
DOI: 10.1364/ao.52.001276
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of phase-only double random phase encoding based on key-space analysis

Abstract: Although initial research shows that double-random phase encoding (DRPE) is vulnerable to known-plaintext attacks that use phase retrieval algorithms, subsequent research has shown that phase-only DRPE, in which the Fourier amplitude component of an image encrypted with classical DRPE remains constant, is resistant to attacks that apply phase retrieval algorithms. Herein, we numerically analyze the key-space of DRPE and investigate the distribution property of decryption keys for classical and phase-only DRPE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…. 23 Anisotropic materials such as cellophane [88] can be used for producing more complex structures. Anisotropy has been induced by attaching small strips of adhesive tape on the two samples; note that the orientation, length and width of the strips are placed at random.…”
Section: Authentication Of Codes Produced With Thin-films Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…. 23 Anisotropic materials such as cellophane [88] can be used for producing more complex structures. Anisotropy has been induced by attaching small strips of adhesive tape on the two samples; note that the orientation, length and width of the strips are placed at random.…”
Section: Authentication Of Codes Produced With Thin-films Techniquesmentioning
confidence: 99%
“…Multiple alternatives have been suggested in order to make optical security systems more robust [17][18][19][20][21]. For instance, the so-called digital optics methods represent a very popular approach in optical-based encryption [22][23][24][25][26][27]. These procedures mimic physical processes by means of digital calculations or combine numerical operations with optical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that a plurality of attacks have been designed to break DRPE systems [23][24][25][26][27][28][29][30], different approaches were suggested to improved security in DRPE. For instance, it has been demonstrated that quantum encryption systems that works with few photons are very secure [31,32].…”
Section: Encryption and Validationmentioning
confidence: 99%
“…Consequently, additional improvements with optical security techniques [16][17][18][19][20][21][22] could be adapted to be used with focused beams. To avoid conventional attacks against the information encrypted in the longitudinal component [23][24][25][26][27][28][29][30], the use of quantum imaging techniques is suggested [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…This area of research includes image encryption [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], authentication [16][17][18][19][20][21][22][23][24], and compression or secure storage [25,26]. Authenticating sensitive information is critical to discovering tampering caused by a miscreant.…”
Section: Introductionmentioning
confidence: 99%